Perbandingan Makna Hutang (Dain) dalam Al-Quran: Analisis makna Dain dalam Tafsir Ibnu Katsir dan Tafsir al-Misbah - Moh. Supriyadi (International Conference on Islamic Economic (ICIE), 2025)
The rapid development of the era has given rise to new problems that need to be solved. The Qur'an as a holy book throughout the ages can certainly provide solutions to every problem, especially those related to debt, but a comprehensive and precise interpretation is needed for every problem that exists. The purpose of this study is to discuss the meaning of "Dain" in the Tafsir of Ibn Kathir and to find out the meaning of "Dain" in the Tafsir of Al-Misbah and to reveal the similarities and differences in the meaning of "Dain" and its relevance in today's life in Surah Al-Baqarah verse 282. This study uses a qualitative approach with a library method. The results show that in carrying out debt-credit transactions, as explained in the Qur'an, first a record or writing must be made. Related to the party who did the writing, Quraisy Shihab and Ibn Kathir in their Tafsir